2021
DOI: 10.3389/fnins.2021.642584
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Stimulation Modulates Visual Perception Without Training

Abstract: Considerable research shows that olfactory stimulations affect other modalities in high-level cognitive functions such as emotion. However, little known fact is that olfaction modulates low-level perception of other sensory modalities. Although some studies showed that olfaction had influenced on the other low-level perception, all of them required specific experiences like perceptual training. To test the possibility that olfaction modulates low-level perception without training, we conducted a series of psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Decreased FC was observed between the area surrounding the anterior as well as the medial dorsal part of thalamus and MVN in patients with a higher degree of parosmia (Par 2–3). A recent study contemplated the role of visual network and olfaction and found that olfaction modulates low-level visual inputs [ 43 ]. The authors of the paper focus on the cross-modal effect of various senses.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased FC was observed between the area surrounding the anterior as well as the medial dorsal part of thalamus and MVN in patients with a higher degree of parosmia (Par 2–3). A recent study contemplated the role of visual network and olfaction and found that olfaction modulates low-level visual inputs [ 43 ]. The authors of the paper focus on the cross-modal effect of various senses.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that exposure to commercially available essential oils in real-time can improve memory, alertness, vigilance, self-perception, pain perception, and mood (Johnson, 2011 ). Similarly, Tsushima et al ( 2021 ) found that exposure to a lemon odorant and vanilla odorant modulated positively and negatively, respectively, low-level visual perception, which suggests some innate characteristics of odorants on perception and cognitive function.…”
mentioning
confidence: 85%
“…The perception and memory processes of human are crossmodal, that is, the information input from different sense organs will interact in a synergistic or antagonistic manner, thereby strengthening the ability to perceive the environment or memory. For example, Tsushima et al found that fragrance can change the human perception of the moving speed of pictures through psychological and physiological experiments [57]. Therefore, optoelectronic synapses with visual-olfactory crossmodal perception for developing biomimetic visual perception and memory are highly desired.…”
Section: Visual-olfactory Crossmodal Perceptionmentioning
confidence: 99%